Extracellular CIRP Upregulates Proinflammatory Cytokine Expression via the NF-kappaB and ERK1/2 Signaling Pathways in Psoriatic Keratinocytes - Xiu Zhang; Shengbang Wang; Wei Wang; Liumei Song; Shuo Feng; Jingping Wang; Tong Kang; Peiwen Yang; Ning Wang; Pengju Yang; Ruimin Bai; Yongping Shao; et al. (Hindawi Limited, 2022)
Psoriasis is a chronic inflammatory skin disease, and elevation of proinflammatory cytokine levels is a critical driver of the pathogenesis of psoriasis. Extracellular cold-inducible RNA-binding protein (eCIRP) has been shown to play a role in various acute and chronic inflammatory diseases. C23, a short peptide derived from CIRP, competitively binds CIRP receptors and reduces damage in inflammatory diseases. However, the effect of eCIRP in psoriasis has not been studied. In the present study, we investigated the role of eCIRP in the expression of proinflammatory cytokines in keratinocytes. Our data show that eCIRP expression was increased in the sera of psoriasis patients and imiquimod- (IMQ-) induced psoriatic mice and cells stimulated with proinflammatory cytokines (IL-1α, IL-17A, IL-22, oncostatin M, and TNF-α; mix M5). Recombinant human CIRP (rhCIRP) promoted the expression of the proinflammatory cytokines TNF-α, IL-6, and IL-8 and the activation of NF-kappaB (NF-κB) and ERK1/2 in cultured keratinocytes. We then found that the above effects of eCIRP could be blocked by C23 in both normal keratinocytes and M5-stimulated psoriatic keratinocytes. In addition, in vivo experiments revealed that C23 could effectively ameliorate IMQ-induced psoriatic dermatitis. TNF-α and IL-6 mRNA expressions were reduced in the skin lesions of mice with C23-treated IMQ-induced psoriasis, and this effect was accompanied by inhibition of the NF-κB and ERK1/2 signaling pathways. In summary, eCIRP plays an important role in the pathogenesis of psoriasis and may become a new target for psoriasis treatment.